2021
DOI: 10.1017/jfm.2021.885
|View full text |Cite
|
Sign up to set email alerts
|

Vesicle dynamics in large amplitude oscillatory extensional flow

Abstract: Although the behaviour of fluid-filled vesicles in steady flows has been extensively studied, far less is understood regarding the shape dynamics of vesicles in time-dependent oscillatory flows. Here, we investigate the nonlinear dynamics of vesicles in large amplitude oscillatory extensional (LAOE) flows using both experiments and boundary integral (BI) simulations. Our results characterize the transient membrane deformations, dynamical regimes and stress response of vesicles in LAOE in terms of reduced volum… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 67 publications
0
7
0
Order By: Relevance
“…Lin et al. 2021), these boundary conditions should be imposed on a section of a channel branch away from the intersection to more accurately model typical experimental set-ups, either by simulating the droplet in the full microfluidic domain or by using a moving-frame construction like the one described in Roure et al. (2023) (see figure 1 c ), in which the frame changes with time as the drop moves and/or deforms.…”
Section: Boundary-integral Formulationmentioning
confidence: 99%
See 2 more Smart Citations
“…Lin et al. 2021), these boundary conditions should be imposed on a section of a channel branch away from the intersection to more accurately model typical experimental set-ups, either by simulating the droplet in the full microfluidic domain or by using a moving-frame construction like the one described in Roure et al. (2023) (see figure 1 c ), in which the frame changes with time as the drop moves and/or deforms.…”
Section: Boundary-integral Formulationmentioning
confidence: 99%
“…Besides the droplet or vesicle size, the dynamics of the problem is strongly affected by changes in shape, especially when the droplets/vesicles undergo large deformations. Although some recent works tackled the deformation of vesicles (Kumar et al 2020a,b;Lin et al 2021) and control of small droplets using a Stokes trap (Narayan et al 2020a,b), the complex dynamics of drop deformation and response to different flow modes have not been simulated. However, recently, the work by Razzaghi & Ramachandran (2023) has shown experimentally that richer flow modes produced by hydrodynamic traps, such as a quadratic flow, can result in interesting drop shapes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, it was found that vesicle relaxation is governed by a double-mode process, with the first stage involving relaxation of the thin lipid nanotube connecting the two spherical bulbs in the dumbbell. , Vesicle dynamics in a time-dependent extensional flow with a single flow-reversal step was previously reported . Recently, vesicle dynamics in large-amplitude oscillatory extensional flow was studied using a combination of precision flow experiments using the Stokes trap and numerical modeling and simulations . Overall, vesicle stretching in extensional flows generally involves distributed viscous forces across the entire membrane for freely suspended bodies in the absence of external forces.…”
Section: Introductionmentioning
confidence: 98%
“…50 Recently, vesicle dynamics in large-amplitude oscillatory extensional flow was studied using a combination of precision flow experiments using the Stokes trap and numerical modeling and simulations. 51 Overall, vesicle stretching in extensional flows generally involves distributed viscous forces across the entire membrane for freely suspended bodies in the absence of external forces. From this view, vesicle deformation in extensional flow is distinct from classical methods used to deform vesicle membranes, e.g.…”
Section: ■ Introductionmentioning
confidence: 99%